Analysis of Kinematic Performance and Research of Dynamics Solution of New Type 4-DOF Parallel Mechanism - Wang Zongping; Zhao Dengfeng; Li Kuan; Zeng Guoying; Li Zhongyang; Yang Guiyang (Jixie chuandong)
A 2UPS-RPS-UPU spatial 4-DOF parallel mechanism is introduced. The inverse kinematics equation of 2UPS-RPS-UPU is presented and the speed variation of the driving rod is solved by velocity projection,and the Jacobi matrix of the mechanism is deduced. The dynamics model of the system is established which based on the Lagrange equations of non-conservative system,which lays the foundation for dynamics analysis. A method to solve Lagrange equation with quickness is presented and combining with the equation characteristics,the part of second-order differential of equation will be simplified to the multiplication,and the first order partial differential will simplified solving through the similar method of differential quotient. The results of the derivation is simulated by using Matlab,and the kinematics and dynamics curves of the mechanism with time and interrelationships are plotted. The 3D model is put into ADAMS for simulation,and finally the ADAMS result is in agreement with the Matlab,which verified the correctness and feasibility of the method and also provides the basis for the further study and solving the similar problem. This study is not only helpful for further study of the mechanism,but also has the certain guiding significance for the design,control and character analysis of related type parallel mechanism.